Cellulose Nanofibril (CNF) Reinforced Starch Insulating Foams. Issue 1621 (7th January 2014) - Yildirim, N.; Shaler, S.M.; Gardner, D.J.; Rice, R.; Bousfield, D.W.
ABSTRACT: In this study, biodegradable foams were produced using cellulose nanofibrils (CNFs) and starch (S). The availability of high volumes of CNFs at lower costs is rapidly progressing with advances in pilot-scale and commercial facilities. The foams were produced using a freeze-drying process with CNF/S water suspensions ranging from 1 to 7.5 wt. % solids content. Microscopic evaluation showed that the foams have a microcellular structure and that the foam walls are covered with CNF`s. The CNF's had diameters ranging from 30 nm to 100 nm. Pore sizes within the foam walls ranged from 20 nm to 100 nm. The materials` densities ranging from 0.012 to 0.082 g/cm 3 with corresponding porosities between 93.46% and 99.10%. Thermal conductivity ranged from 0.041 to 0.054 W/m-K. The mechanical performance of the foams produced from the starch control was extremely low and the material was very friable. The addition of CNF's to starch was required to produce foams, which exhibited structural integrity. The mechanical properties of materials were positively correlated with solids content and CNF/S ratios. The mechanical and thermal properties for the foams produced in this study appear promising for applications such as insulation and packaging.